An Integrated Switched Injection-Locked Oscillator for Pulsed Angle Modulated Ultra Wideband Communication and Radar Systems - Eßwein, Alexander; Carlowitz, Christian; Fischer, Georg; Vossiek, Martin; Weigel, Robert; Ußmüller, Thomas (IEEE International Conference on Ultra-Wideband, ICUWB 2012, 2012)
This paper describes an integrated switched injection-locked oscillator (SILO) circuit for use in pulsed angular modulated ultra wideband communication and radar systems. The circuit consists of two active baluns for single-ended to differential and differential to single-ended conversion, a Schmitt-trigger with modified current mirror load for current peak generation and a simple cross-coupled oscillator for signal generation. It has an externally controllable pulse repetition rate and a pulse duration of approx. 1ns. During operation it consumes 33mA at 3.3V supply voltage, while generating a 370 mVpp signal. The generated signal has a 10dB-bandwidth of over 2GHz at 7.5 GHz center frequency. Measurement results with an external baseband generator are shown. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEH.aninte
Keywords: Injection-Locking; Integrated Circuit; Pulse Generation; Pulsed Frequency Modulated Radar; Radar; VCO